Zinc oxide-catalyzed UV-photodegradation of cyhalothrin: A kinetic analysis - Osumba, Seth Otieno; Adongo, John Onyango; Omolo, Josiah Ouma (European Journal of Chemistry, 2025)
In this study, we present kinetic studies of the photodegradation of cyhalothrin (CyH) under ultraviolet (UV) irradiation and the photocatalytic activity of zinc oxide (ZnO) in UV-assisted photodegradation. CyH in an acetone solvent was periodically exposed to UV254 nm radiation light with a surface power density of 48 W/cm2. The photodegradation experiments were conducted by acquiring periodic wavelength-scan spectroscopic data using a double beam ultraviolet-visible (UV-vis) spectrophotometer and plotting the real-time absorbance data to monitor the reaction coordinate. Under our optimized conditions at room temperature of 26.5 °C, atmospheric pressure of 76.6 mmHg, CyH (5.0 ppm) in the 70% acetone solvent with pH = 6.8 and dose of ZnO (25 ppm) exhibited typical photodegradation efficiencies between 81.9 and 90.3 % within the first 1,200 seconds of UV irradiation. Spectroscopic data showed that the ZnO solution significantly elevated the UV-assisted photodegradation rate of CyH by about 7.03 - 7.18 times more than that of UV-only-mediated CyH photodegradation. The result confirmed and characterized the photocatalytic activity of ZnO. Under the optimized measurement conditions, the rate of the ZnO-catalyzed photodegradation of CyH was found to follow the first-order rate law (RSq. = 0.999).